Accounting for corner flow unifies the understanding of droplet formation in microfluidic channels - Piotr M. Korczyk (Nature Portfolio, 2019)
T-junctions are a tool for droplet generation; they are well-described by models that distinguish for squeezing and jetting regimes for different capillary numbers. By considering the usually neglected corner flow, the authors identify an additional leaking regime for very low capillary numbers.